TANGGUNG GUGAT PENGELOLA HOTEL TERHADAP HILANGNYA BARANG PRIBADI TAMU HOTEL - Ruslan, Herlina; Borman, M. Syahrul; Handayati, Nur; Sidarta, Dudik Djaja (Universitas Negeri Makassar, 2025)
The standard clause which states